1998
DOI: 10.2307/3284712
|View full text |Cite
|
Sign up to set email alerts
|

Lyme Disease Spirochetes in Ticks from Northeastern China

Abstract: During May 1996, field surveys on Lyme disease spirochetes were conducted in Beijing, Shenyang, Fushun, and Inner Mongolia in northeastern China. The ticks collected consisted of 3 genera and 12 species. Of these, Ixodes persulcatus was dominant in sun-exposed vegetation in forests in Inner Mongolia; 57 Borrelia strains (55/123 unfed adults and 2/5 immature stages fed on a rodent) were obtained from this tick by BSK culture. Additionally, 2/2 Apodemus peninsulae were positive. Ixodes nipponensis, Ixodes pavlov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 1 publication
0
22
0
Order By: Relevance
“…Thus, our findings reconfirmed a strong affinity between birds and B. garinii. Although not many Korean or Chinese borreliae have been clearly characterized, most Korean and northeastern Chinese strains isolated in previous surveys (11,14,34) were identified as B. garinii with pattern B or pattern C or B. afzelii with pattern D (14, T. Masuzawa, unpublished data); only two strains, 935T and ChY13p, were identified as having pattern R. Such a unique pattern had not been observed previously among isolates in Japan and far-eastern Russia. Our findings revealed that strains Fi14f and Fi24f, characterized in the pattern R group, were closely related to strains 935T in Korea and ChY13p in China, respectively.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Thus, our findings reconfirmed a strong affinity between birds and B. garinii. Although not many Korean or Chinese borreliae have been clearly characterized, most Korean and northeastern Chinese strains isolated in previous surveys (11,14,34) were identified as B. garinii with pattern B or pattern C or B. afzelii with pattern D (14, T. Masuzawa, unpublished data); only two strains, 935T and ChY13p, were identified as having pattern R. Such a unique pattern had not been observed previously among isolates in Japan and far-eastern Russia. Our findings revealed that strains Fi14f and Fi24f, characterized in the pattern R group, were closely related to strains 935T in Korea and ChY13p in China, respectively.…”
Section: Discussionmentioning
confidence: 79%
“…Ticks were removed with forceps and placed in separate glass vials containing moist sanitary cotton. The stage and species of each tick were identified as described by Takada (34).…”
Section: Methodsmentioning
confidence: 99%
“…A previous study reported 64.4% B. garinii and 35.6% B. afzelii based on a PCRrestriction fragment length polymorphism analysis of 45 B. burgdorferi isolates from this area. 18 Whether the coinfection was associated with B. burgdorferi genospecies remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16] Northeastern China is highly endemic for Lyme disease, 17 where the infection rate of B. burgdorferi in adult I. persulcatus ticks can be as high as 44.1%. 18 Recently, the presence of A. phagocytophila in ticks from the region has been reported. 12 Therefore, an extensive study was carried out to confirm the previous findings, and to investigate coinfection of I. persulcatus ticks with A. phagocytophila and B. Burgdorferi.…”
Section: Introductionmentioning
confidence: 99%
“…After that, scientific papers using the invalid name have been gradually increased (Takada et al, 1998;Fujita et al, 2000;Yoshimoto et al, 2009;Yokoyama et al, 2012;Tagawa et al, 2013), but a few researchers used names of H. japonica and H. jezoensis for the same organism (Ozawa and Kadosaki, 1996;Ito and Takahashi, 2001). Such a confused and strange situation is still continuing, particularly in Hokkaido.…”
Section: Introductionmentioning
confidence: 99%